1992
DOI: 10.1287/inte.22.5.59
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Diet Model in Managing Food Systems

Abstract: To cite this article: Lilly M. Lancaster, (1992) The Evolution of the Diet Model in Managing Food Systems. Interfaces 22(5):59-68. http:// dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
0
8
0
3
Order By: Relevance
“…This dynamic food menu environment must be tackled by caterers in the decision making process in order to satisfy all stakeholders. Thus, the proposed menu planning prototype is flexible in managing these changes in terms of the number of menu items involved, the price of menu items, the available budget and the caterer's cooking ability which was not taken into account by the previous studies which reported by Smith, (1959), Armstrong and Sinha (1974), Balintfy (1975), Bassi, (1976, Foytik (1981), McCann-Rugg et al (1983), Silberberg (1985), Benson and Morin (1987), Lancaster (1992), Sklan and Dariel (1993), Fletcher et al (1994), Leung et al (1995), Gallenti (1997), Westrich et al (1998), Garille and Gass (2001) and Asyikin and Razali (2011). Based on the results, the process of generating the menu can take up to more than a week within seconds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dynamic food menu environment must be tackled by caterers in the decision making process in order to satisfy all stakeholders. Thus, the proposed menu planning prototype is flexible in managing these changes in terms of the number of menu items involved, the price of menu items, the available budget and the caterer's cooking ability which was not taken into account by the previous studies which reported by Smith, (1959), Armstrong and Sinha (1974), Balintfy (1975), Bassi, (1976, Foytik (1981), McCann-Rugg et al (1983), Silberberg (1985), Benson and Morin (1987), Lancaster (1992), Sklan and Dariel (1993), Fletcher et al (1994), Leung et al (1995), Gallenti (1997), Westrich et al (1998), Garille and Gass (2001) and Asyikin and Razali (2011). Based on the results, the process of generating the menu can take up to more than a week within seconds.…”
Section: Discussionmentioning
confidence: 99%
“…This model, as in most operation research models have been set up on the traditional fundamental assumption that the decision maker seeks to optimize a single objective function. The problem has continued to be investigated by scientists and nutritionists (Smith, 1959;Armstrong and Sinha, 1974;Balintfy, 1975;Bassi, 1976;Foytik, 1981;McCann-Rugg et al, 1983;Silberberg, 1985;Benson and Morin, 1987;Lancaster, 1992;Sklan and Dariel, 1993;Leung et al, 1995;Gallenti, 1997;Westrich et al, 1998;Garille and Gass, 2001;Martinez-Alfaro, 2003;Cadenas et al, 2004). Therefore in this study, the main studies are to expend the current knowledge in menu planning and diet problems focusing on Malaysian recipes, minimizing the cost, fulfill the nutritional requirements and serve variety of food serve each day.…”
Section: Introductionmentioning
confidence: 99%
“…Garille and Gass (2001) points out the inadequacies of Stigler's minimal subsistence diet in terms of palatability, variety, and overall adequacy. In her article describing the evolution of the diet model into a more acceptable menu-planning approach, Lancaster (1992) observes that "the solution to the least cost diet is the equivalent of the human dog biscuit." The combination of food items may not be desirable for consumption but nutrition and costs are controlled.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This problem is cited in many operations research textbooks. The evolution of different models (linear, non-linear and stochastic) used for diet formulation is discussed by Lancaster (1992aLancaster ( , 1992b. Goal and multi-objective optimization models have also been introduced, see for example Tozer and Stokes (2001), Castrodeza et al (2005), Rehman and Romero (1987) and references therein.…”
Section: Classic Feed Formulation Modelmentioning
confidence: 99%